PENGETAHUAN PENGOBATAN MANDIRI PENGGUNAAN JERUK NIPIS (CITRUS AURANTIFOLIA) SEBAGAI OBAT BATUK PADA MASYARAKAT DESA KURIPAN KIDUL - Asniatu Umi Maghfiroh; Ainun Mutoharoh; Yulian Wahyu Permadi; Dwi upa Bagus Pambudi (Bapperida Kabupaten Pekalongan, 2022)
Cough is a common disease that generally gains less attention since people think that cough can disappear by itself without any particular treatment. Cough requires treatment if its symptoms disturb the patients a lot. Patients can treat cough by doing self-medication. Self-medication is the selection and use of drugs for minor illnesses or self-recognized symptoms without any prescription from doctors. The purpose of this study was to determine the correlation of the understanding level of successful clinical outcomes and self-medication using lime as a cough medicine. This research employed a survey method with questionnaires distributed directly. The sampling technique being used was purposive sampling. The data were analysed with univariate and bivariate analyses with Chi Square test. The results of this study showed that the respondents had good level of understanding (99%). However, there was no significant correlation neither between the understanding level and clinical outcomes, nor between the understanding level and self-medication with the probability of Chi Square of 0.568 < Chi Square of 3.841 and the value of Chi Square of 3.199 < Chi Square of 7.581.